Immune Tolerance Therapy for Haemophilia A Patients with Acquired Factor VIII Alloantibodies: Comprehensive Analysis of Experience at a Single Institution - Smith, M. P.; Spence, K. J.; Waters, E. L.; Beresford-Webb, R.; Mitchell, M. J.; Cuttler, J.; Alhaq, A.; Brown, S. A.; Savidge, G. F. (Thrombosis and Haemostasis, 1999)
Eleven children with severe haemophilia A associated with the IVS 22 inversion and acquired high titre neutralising antibodies to factor VIII underwent immune tolerance induction. HLA class I and high resolution class II type is detailed for each patient. A three phase approach to immune tolerance induction was used. During phase 1, which lasted a median of six weeks, patients received factor VIII 100 IU/kg twice daily. Phase 2 comprised a factor VIII dose reduction to 100 IU/kg once daily, and continued for a median duration of 14 weeks. Subsequently 10 of the 11 patients satisfied the criteria of absent factor VIII neutralising activity by the Bethesda method, and a factor VIII elimination half life of greater than 5 h, allowing progression to phase 3, a further factor VIII dose reduction to 50 IU/kg three times weekly. A model for dose reduction as factor VIII tolerance evolves, based on pharmacokinetic analysis, is described.